1979
DOI: 10.1007/bf02812022
|View full text |Cite
|
Sign up to set email alerts
|

Critical fracture stress and fracture strain models for the prediction of lower and upper shelf toughness in nuclear pressure vessel steels

Abstract: Critical fracture stress and stress modified fracture strain models are utilized to describe the variation of lower and upper shelf fracture toughness with temperature and strain rate for two alloy steels used in the manufacture of nuclear pressure vessels, namely SA533B-1 (HSST Plate 02) and SA302B (Surveillance correlation heat). Both steels have been well characterized with regard to static and dynamic fracture toughness over a wide range of temperatures (-190 to 200~ although valid JIc measurements at uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(57 citation statements)
references
References 24 publications
2
55
0
Order By: Relevance
“…Unstable crack propagation in metallic alloys begins when a critical stress is reached over a microstructurally significant distance. Some researchers have reported this distance to be in the order of 100 to 300 micrometers, depending on alloy chemistry, testing conditions and heat treatment [55]. If this interpretation is accepted, it may also be possible to say that a number of damage sites of length a 0 (sub-units of the critical length) join over the microstructurally significant distance, and thereby, lead to unstable crack propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Unstable crack propagation in metallic alloys begins when a critical stress is reached over a microstructurally significant distance. Some researchers have reported this distance to be in the order of 100 to 300 micrometers, depending on alloy chemistry, testing conditions and heat treatment [55]. If this interpretation is accepted, it may also be possible to say that a number of damage sites of length a 0 (sub-units of the critical length) join over the microstructurally significant distance, and thereby, lead to unstable crack propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitatively, such failures are described by a criterion in which the continuum crack-tip strain exceeds a critical value, ε * , over a characteristic distance, l * , ahead of the crack tip [57,58]. This characteristic distance is generally the distance spanned by a microstructural crack emanating from the main crack.…”
Section: Fracture Mechanismsmentioning
confidence: 99%
“…This characteristic distance is generally the distance spanned by a microstructural crack emanating from the main crack. Based on the Hutchinson-Rice-Rosengren (HRR) crack-tip field solutions, the critical stress intensity factor for crack extension can be related to the critical strain and the characteristic distance as [57,58] …”
Section: Fracture Mechanismsmentioning
confidence: 99%
“…Based on the model proposed by Richie, Knott, and Rice (RKR) [2,3], brittle fracture occurs when the stress state exceeds σ f at a characteristic distance (r c ) about twice the grain size away from the crack tip. Further investigation showed that, even the cleavage fracture mechanism during ductile-brittle transition may change with the specimen geometry, temperature, loading rate, prestrain, and material composition, it appears that σ f is a stable quantity and may be used as a material toughness parameter [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%